EKSISTENSI ARSITEKTUR BALI DALAM ARSITEKTUR KEKINIAN STUDI KASUS : KUTA CENTRAL PARK - Tjokorda Istri Praganingrum; Ida Bagus Suryatmaja (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
The growth of population and the development of economic level in this global era indirectly have an enormous impact on the development of architecture in Bali. As a tourist destination by both domestic and foreign tourists, the architecture in Bali has grown and is difficult to control. The entry of various foreign elements will ultimately dominate the local architecture of Bali. This has begun to be seen from the emergence of various views of the building with the current architecture that combines various styles to be the center of attention. One of the locations that show it is Kuta Central Park. This study was conducted to find out how the existence of Traditional Balinese Architecture against foreign elements that tend to dominate. The method used is qualitative descriptive analysis technique. This analysis will be directed to a descriptive explanation of how the shape of an architecture is located in the research location, and how it correlates with the effort to maintain the traditional Balinese architecture. The result of the research has shown that the combination of architectural style in the research location resulted in the absence of traditional characteristics that should still be displayed to provide local cultural identity. The mixing of architectural styles in the research location decreases the existence of local Balinese architectural features. The look of local architecture is no longer the main point of design emphasis on research sites. The 'contemporary' look that brings together multiple styles makes local architecture a mere complement to the necessary design.